The Effect of Islamic Financial Inclusion on Economic Growth: A Case Study of Islamic Banking in Indonesia - Fauziyah Adzimatinur; Vigory Gloriman Manalu (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research aims to examine the effects of financial inclusion in Islamic banking on economic development in Indonesia. The economic growth indicator is represented by the Industry Production Index (IPI) while the financial inclusion indicator is represented by the amount of Third Party Funds, the amount of financing, the number of Third Party Funds accounts, and the number of financing accounts. The data used is time series from January 2011 to February 2020. The Vector Error Correction Model (VECM) is used to analyze the data. The results show that in the long run, inflation has a positive effect, while in the short term, inflation has a positive effect on lag one and has a negative effect on lag 2. While the financial inclusion indicator shows that the financial inclusion of Islamic banking in Indonesia has a positive effect on economic growth.